Peran Organisasi Remaja Masjid Al-Waqif Sempurna (Remals) Dalam Membentuk Akhlak Remaja di Kelurahan Sudirejo I Kecamatan Medan Kota - Adelia Fitri Lubis; Azizah Hanum OK (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The research that has been carried out entitled "The Role of the Al-Waqif Perfect Mosque Youth Organization (REMALS) in Forming Youth Morals in Sudirejo I Village, Medan City District", this study aims: (1) to find out the efforts of the Al-Waqif Perfect mosque youth organization in running the program work in Environment II, Sudirejo I Village, Medan City District, (2) to find out the obstacles of the youth of the Al-Waqif Perfect mosque in shaping the morals of youth in Environment II, Sudirejo I Village, Medan City District. This research is a descriptive qualitative research method. In the data collection process, researchers used three data collection techniques, namely observation, interviews and documentation. From the results of the study it can be concluded that: (1) the efforts of the youth of the Al-Waqif Perfect mosque in carrying out their work program have a very important effort that is no longer limited to an organization that only studies and explores the religious teachings of youth, but becomes a space for them to take part and carry out activities social, cultural, educational, community and humanitarian. (2) the constraints of the youth organization of the Al-Waqif Perfect mosque in shaping the morals of youth in the Sudirejo I Village, Medan City District, namely the busyness of some of the administrators because of work there are also those who are still studying at school, decreased enthusiasm, lack of awareness of duties and responsibilities in broadcasting Islamic law. Keywords: Mosque Youth, Morals, Organizational Role